1993
DOI: 10.1002/jctb.280570208
|View full text |Cite
|
Sign up to set email alerts
|

Screening of white rot fungi for the treatment of olive mill waste‐waters

Abstract: Several white rot fungi were evaluated for their ability to decolorize olive mill waste-waters (OMW). Among these, Phanerochaete chrysosporium showed the highest potential for the biological depollution of OMW. Approximately 65 % of the color and 73 % of the chemical oxygen demand (COD) were removed by P. chrysosporium strain HD. Phlebia radiata, Dichomitus squalens, Polyporus frondosus and Coriolus versicolor could also decolorize the OMW but to a lesser extent. The different abilities of these white rot fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 24 publications
1
28
0
1
Order By: Relevance
“…A B.O.D. decrease of about 90%, from 101.7 to 10.7 g l -1 , was also obtained; this finding is consistent with data previously reported on the growth of single Pleurotus fungi (Fountoulakis et al 2002;Isadori et al 2004;Kissi et al 2001;Rigoni-Stern et al 1988;Sayady and Ellouz 1993;Maullu et al 1999;Pompei et al 1994;Sanjust et al 1991). The final B.O.D.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A B.O.D. decrease of about 90%, from 101.7 to 10.7 g l -1 , was also obtained; this finding is consistent with data previously reported on the growth of single Pleurotus fungi (Fountoulakis et al 2002;Isadori et al 2004;Kissi et al 2001;Rigoni-Stern et al 1988;Sayady and Ellouz 1993;Maullu et al 1999;Pompei et al 1994;Sanjust et al 1991). The final B.O.D.…”
Section: Discussionsupporting
confidence: 93%
“…In fact untreated OMWW are able to change the microbial composition of the soil through their antibacterial activity (Borya et al 1995;Tardioli et al 1997) and to produce phytopathogenic effects due to their high toxicity (Bressan et al 2004). In recent years, some methods have been proposed for OMWW bioremediation, such as chemical or microbiological treatment (Fountoulakis et al 2002;Isadori et al 2004;Kissi et al 2001;Maullu et al 1999;RigoniStern et al 1988;Sayady and Ellouz 1993). Some systems were also patented (Brueggemann and Huebner 2002;Catalano and De Nobili 2002;Reverso 1999).…”
Section: Introductionmentioning
confidence: 97%
“…phenolic compounds [25,26]. Dhouib et al [27] tested a pilot-scale fungal pre-treatment of raw OMW using P. chrysosporium followed by anaerobic digestion, without any addition of nutrients or alkalinity.…”
Section: (Pre)-treatment To Remove Polyphenolic Componentsmentioning
confidence: 99%
“…Chrysosporium is one of the organisms whose ligninolytic enzyme system has been studied extensively. Because of its high ligninolytic activity, rapid growth, and ability to produce asexual spores, several biotechnological applications were tested using this particular species (Sayadi and Ellouz, 1992;1993).…”
Section: Introductionmentioning
confidence: 99%
“…A recent work has shown that the P. Chrysosporium species is able to degradate a wide variety of phenolic compounds (Sayadi and Ellouz, 1992;1993). Besides P. Chrysosporium produces two types of extra-cellular peroxidases involved in lignin biodegradation:…”
Section: Introductionmentioning
confidence: 99%